Faster life history strategy manifests itself by lower age at menarche, higher sexual desire, and earlier reproduction in people with worse health - Sýkorová, Kateřina; Flegr, Jaroslav (Scientific reports, 2021)
Factors which indicate lower life expectancy also induce switching to a faster life strategy, that is, a higher investment in current reproduction at the expense of future reproduction and body maintenance. We tested a hypothesis according to which impairment of individual health serves as a signal for switching to a faster life strategy using online-gathered data from 32,911 subjects. Worse health was associated with lower age at menarche and earlier initiation of sexual life in women and higher sexual desire and earlier reproduction in both sexes. Individuals with worse health also exhibited lower sexual activity, lower number of sexual partners, and lower total number of children. These results suggest that impaired health shifts individuals towards a faster life strategy but also has a negative (physiological) effect on behaviours related to sexual life. Signs of a faster life strategy were also found in Rh-negative men in good health, indicating that even just genetic predisposition to worse health could serve as a signal for switching to a faster life strategy. We suggest that improved public health in developed countries and the resulting shift to a slower life strategy could be the ultimate cause of the phenomenon of demographic transition.
Keywords: Young Adult; zvláštnosti životní historie; menarche; Male; Menarche; Libido; mladý dospělý; Reproduction; Adult; Age Factors; dospělí; libido; mužské pohlaví; rozmnožování; Health Status; lidé; ženské pohlaví; Humans; Sexual Behavior; sexuální chování; věkové faktory; zdravotní stav; Female; lidé středního věku; Life History Traits; Middle Aged